System pieczy zastępczej w Wielkiej Brytanii a polskie rodziny zastępcze - Walancik-Ryba , Karolina (Studia Edukacyjne, 2019)
The article “Foster care system in Great Britain and Polish foster families” is devoted to the British system of foster care, which allows to create a foster family by Polish citizens. The article discusses the main principles on which the foster care and its forms are based. National standards and requirements for candidates to foster families were presented as well as issues related to the implementation of foster care, including these regarding support for foster parents and housing or financial requirements.